2010
DOI: 10.3390/en3030462
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Development of Electricity-Generating Technologies: A Literature Review

Abstract: Electricity is perhaps the most versatile energy carrier in modern economies, and it is therefore fundamentally linked to human and economic development. Electricity growth has outpaced that of any other fuel, leading to ever-increasing shares in the overall mix. This trend is expected to continue throughout the following decades, as largeespecially rural-segments of the world population in developing countries start to climb the "energy ladder" and become connected to power grids. Electricity therefore deserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 249 publications
(516 reference statements)
0
71
0
5
Order By: Relevance
“…The variability of production and grid integration is commonly suggested as the main barriers for implementation of renewable energy and it has even been suggested that this factor limits penetration rates of wind energy to 20 % of electricity production (Lenzen, 2010). These factors are discussed in more detail in other studies (Trainer, 2013(Trainer, , 2012.…”
Section: Other Potential Constraints For Renewable Energymentioning
confidence: 99%
“…The variability of production and grid integration is commonly suggested as the main barriers for implementation of renewable energy and it has even been suggested that this factor limits penetration rates of wind energy to 20 % of electricity production (Lenzen, 2010). These factors are discussed in more detail in other studies (Trainer, 2013(Trainer, , 2012.…”
Section: Other Potential Constraints For Renewable Energymentioning
confidence: 99%
“…Nuclear power increases production from about eight quads to around twenty-six quads. Technically, despite considerable lead times in developing new nuclear power plants, this ramp-up is feasible within the forty-year analysis horizon of this research [60][61][62][63]. Some legislators and policy makers in Washington, DC are already advocating for one-hundred new nuclear reactors by 2030, which would substantially meet the scenario's requirements.…”
Section: Scenario Design Assumptions Technology and Social Change Assmentioning
confidence: 99%
“…According to SGCC [7], the grid reinforcement investment of the Three Gorges power plants amounted to 34.4 billion Yuan (about 5 billion US dollars). This could be a lot higher in the case of wind power due to a number of reasons: First, the total generation capacity of Three Gorges project is approximately 18.2 GW at this moment and will reach 22.4 GW when fully operating [8], whilst the total generation capacity of the massive wind farms amount to over 100GW. Hence, more transmission capacities are required.…”
Section: Power Grid Investmentmentioning
confidence: 99%
“…In other words, the displacement of traditional thermal power plants with more sustainable energy sources is necessary to reduce the overall CO 2 emissions in the power system; however, the loss of energy efficiency in coal-fired plants due to compensating fluctuations in the wind powered output will result in higher CO2 emissions [52], which might cancel out the part of the emission savings of wind energy. For example, Lenzen [8] concluded that between 35 and 75g of CO 2 6 One recent large-scale electricity shortage happened in April and May 2011 which are not the normal peak load season in a number of provinces. A large number of thermal power plants were shut down for maintenance.…”
Section: Coal As Backup: One Step Forward Two Steps Backmentioning
confidence: 99%